Preparing digital advancements in Pasteur Subdistrict cooperatives - Arfie Aziz; Aldilla Iradianty; Vanya Rifdy (Journal of Community Service and Empowerment, 2024)
The digital economy presents significant opportunities for cooperatives to improve their governance and achieve Sustainable Development Goal (SDG-s) 8, which promotes decent work and inclusive economic growth. As business entities based on economic democracy, cooperatives have the potential to drive the digital economy and enhance the well-being of their members. However, cooperatives in Pasteur, West Java, face various governance challenges, including inadequate bookkeeping, member arrears on savings and loans, and low digital literacy. These hinder the performance and development of the cooperatives. A series of training programs on cooperative governance and human resource management were designed to address these challenges. The program also aimed to improve the digital literacy of cooperative leaders and members and assist them in managing financial and operational aspects more transparently, accountably, and efficiently. The training program proved effective in enhancing the knowledge and skills of cooperative leaders and members in utilizing digital applications for good governance. This led to positive outcomes such as improved bookkeeping, increased savings and loan repayment rates, and more participative and transparent decision-making.